The Use of YouTube Videos in English Language Teaching: A Perspective of Indonesian Undergraduate Students Majoring in English Language Education - Ahmad Jailani (J-SHMIC : Journal of English for Academic, 2022)
This study aims to investigate undergraduate students’ perspective toward the use of YouTube in online and face-to-face learning in which the videos used were made specifically by the lecturer for learning syntax. This study employed a descriptive quantitative method. The data were obtained by distributing survey-based questionnaires to 17 participants studying at a college majoring English Language Education. The results show that participants have strongly positive perspective toward the use of YouTube in both online and face-to-face learning. On their perspective, YouTube videos made are relevant to the course being studied; attractive for its convenience, affordability and accessibility; and effective to help them understand the lesson. It also motivates them to learn well and to participate in the class. So, it is better for lecturers to have a YouTube channel with their own learning videos to support their students in both face-to-face and online learning.